Studi Kasus Lingkungan Keluarga Di Desa Pejanggik : Pola Pembiasaan Pemecahan Masalah Bagi Anak Usia Dini - Sanusi, Ahmad; Muqowwim, Muqowwim; Munastiwi, Erni (Jurnal Golden Age, 2020)
Getting used to solving problems independently for children is very important for their lives. So that in this case children should be taught as early as possible so that children are accustomed to addressing the problems they face. As for the problems that are commonly found in early childhood are like shy, not confident, unable to hold back his emotions such as crying and angry, and not confident in their potential. In this study, researchers aimed to find out how the patterns or strategies of parents to get children used to solving problems independently in the family environment. To get the expected results in this study, researchers used a qualitative method with a case study approach. The data collection techniques used in this study are observation, interviews and documentation. Based on the results of research conducted related to the pattern of habitual problem solving for early childhood in the family environment researchers can find patterns of habituation carried out by parents or families are 1) Give children a sense of comfort, 2) Know the principles of child development, 3) Establish communication with good, 4) Give an example, 5) Sharpen children's abilities, 6) Give freedom not to interfere, 7) Give children freedom or not too meddle.